On oscillation of nonlinear second order differential equation with damping term - Kirane, M; Rogovchenko, YV (Elsevier Science Inc, 2001)
We present new oscillation criteria for the second order nonlinear differential equation with damping. Our theorems are stated in general form; they complement and extend related results known in the literature. The relevance of our results is illustrated with a number of examples. To facilitate computations in these examples, we use Mathematica(R), a symbolic computer language. (C) 2001 Elsevier Science Inc. All rights reserved.
Keywords: second order nonlinear differential equation; damping term; oscillation; integral averaging technique